Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Variation in Polycyclic Aromatic Compound (PAC) Concentrations in a Norway Spruce Stand Close to a Major Traffic Route—Influence of Distance and Season - Jenny Klingberg; Bo Strandberg; Maria Grundström; Henrik Sjöman; Göran Wallin; Håkan Pleijel (Water, Air, & Soil Pollution, 2023)
Air concentrations of polycyclic aromatic compounds (PACs) were measured in a Norway spruce ( Picea abies ) stand at four different distances from a major traffic route near Gothenburg, Sweden, during summer and winter 2019, using passive samplers. In total, the concentrations of 32 polycyclic aromatic hydrocarbons (PAHs) and six dibenzothiophenes (DBTs) and NO 2 were analysed. PAC air concentrations were on average 2.5 times higher during the winter compared to the summer. All investigated PAH categories and compounds as well as dibenzothiophene declined linearly with the logarithmic distance from the traffic route. This indicates that the length of pollutant pathways through vegetation is a valid proxy to assess health risks of traffic-related PAC pollutants. Concentrations of heavier PAHs declined faster (concentration at site furthest away from the road was 6% and 33% of concentration at site closest to road, for summer and winter respectively) with increasing distance from traffic compared to lighter PAHs (63% and 68% for summer and winter respectively). As a result, the mix of PAHs changed with the depth into the forest stand (i.e. distance from the road) with potential effects on the toxicity as well as on diagnostic ratios used for source attribution. This is likely caused by different deposition rates among the PAH compounds to the vegetation surfaces, although the exact mechanism needs to be further investigated. This study provides new information that can improve air quality risk assessment and limit the exposure of the population to toxic air pollutants such as PACs.

Underground emissions and miners’ personal exposure to diesel and renewable diesel exhaust in a Swedish iron ore mine - Louise Gren; Annette M. Krais; Eva Assarsson; Karin Broberg; Malin Engfeldt; Christian Lindh; Bo Strandberg; Joakim Pagels; Maria Hedmer (International Archives of Occupational and Environmental Health, 2022)
Purpose Underground diesel exhaust exposure is an occupational health risk. It is not known how recent intensified emission legislation and use of renewable fuels have reduced or altered occupational exposures. We characterized these effects on multipollutant personal exposure to diesel exhaust and underground ambient air concentrations in an underground iron ore mine. Methods Full-shift personal sampling (12 workers) of elemental carbon (EC), nitrogen dioxide (NO 2 ), polycyclic aromatic hydrocarbons (PAHs), and equivalent black carbon (eBC) was performed. The study used and validated eBC as an online proxy for occupational exposure to EC. Ambient air sampling of these pollutants and particle number size distribution and concentration were performed in the vicinity of the workers. Urine samples (27 workers) were collected after 8 h exposure and analyzed for PAH metabolites and effect biomarkers (8-oxodG for DNA oxidative damage, 4-HNE-MA for lipid peroxidation, 3-HPMA for acrolein). Results The personal exposures (geometric mean; GM) of the participating miners were 7 µg EC m −3 and 153 µg NO 2 m −3 , which are below the EU occupational exposure limits. However, exposures up to 94 µg EC m −3 and 1200 µg NO 2 m −3 were observed. There was a tendency that the operators of vehicles complying with sharpened emission legislation had lower exposure of EC. eBC and NO 2 correlated with EC, R = 0.94 and R = 0.66, respectively. No correlation was found between EC and the sum of 16 priority PAHs (GM 1790 ng m −3 ). Ratios between personal exposures and ambient concentrations were similar and close to 1 for EC and NO 2 , but significantly higher for PAHs. Semi-volatile PAHs may not be effectively reduced by the aftertreatment systems, and ambient area sampling did not predict the personal airborne PAHs exposure well, neither did the slightly elevated concentration of urinary PAH metabolites correlate with airborne PAH exposure. Conclusion Miners’ exposures to EC and NO 2 were lower than those in older studies indicating the effect of sharpened emission legislation and new technologies. Using modern vehicles with diesel particulate filter (DPF) may have contributed to the lower ambient underground PM concentration and exposures. The semi-volatile behavior of the PAHs might have led to inefficient removal in the engines aftertreatment systems and delayed removal by the workplace ventilation system due to partitioning to indoor surfaces. The results indicate that secondary emissions can be an important source of gaseous PAH exposure in the mine.

fMRI memory assessment in healthy subjects: a new approach to view lateralization data at an individual level - Maria Strandberg; Christina Elfgren; Peter Mannfolk; Johan Olsrud; Lars Stenberg; Danielle van Westen; Elna-Marie Larsson; Ia Rorsman; Kristina Källén (Brain Imaging and Behavior, 2011)

MHC class II polymorphism is associated with a canine SLE-related disease complex - Maria Wilbe; Päivi Jokinen; Christina Hermanrud; Lorna J. Kennedy; Erling Strandberg; Helene Hansson-Hamlin; Hannes Lohi; Göran Andersson (Immunogenetics, 2009)